Use of special exercises for the development of motor qualities and the formation of technical and tactical actions of defenders 13–14 years in the preparatory period - Yaroslav Kraynik; Vyacheslav Mulik; Daria Okun; Svyatoslav Koval (Слобожанський науково-спортивний вісник, 2019)
Purpose: to develop the content of training programs for the extreme and central defenders using special exercises in accordance with the game role and determine the effectiveness of their use in young football players 13–14 years old. Material & Methods: the study involved young football players of 13–14 years old FC "Arsenal" in Kharkiv in the amount of 10 athletes during a one-year macrocycle (2018–2019). In the process of research, pedagogical observation and determination of quantitative and qualitative technical and tactical actions during the match, methods of mathematical statistics were used. Results: the influence of the complexes of special running and jumping exercises, which were additionally used by the wing back and central defenders in accordance with the game role, on the quantitative and qualitative indicators of the game activity of young football players of 13–14 years is determined. Conclusions: the results obtained experimentally confirmed the effectiveness of the use of specialized running and jumping exercises separately for the extreme and central defenders, which increases the level of their performance of technical and tactical actions.